Recent status on carbohydrate metabolizing enzyme inhibitors in regulation of diabetes: a mechanism based review - Sinha, Durgeshnandani; Satapathy, Trilochan; Kumar Dewangan, Mehendra; Kumar, Arvind; Roy, Amit (Creative Pharma Assent, 2015)
The important therapeutic approach for treating type 2 diabetes mellitus is to decrease the post-prandial glucose levels which could be done by decreasing the absorption of glucose through the inhibition of the carbohydrates-hydrolyzing enzymes such as α-amylase and α-glucosidase present in the small intestinal brush border that are responsible for the breakdown of oligosaccharides and disaccharides into monosaccharide’s and suitable for absorption. Inhibition of α-amylase generally considered as strategy for the treatment of disorders in carbohydrate uptake, such as diabetes and obesity. Among the marketed allopathic preparations carbohydrates-hydrolyzing enzymes Inhibitors like acarbose, voglibose etc delay carbohydrate digestion and prolong overall carbohydrate digestion time, causing a reduction in the rate of glucose absorption and consequently blunting the postprandial plasma glucose rise. Some of the plants are also considered as an important source of chemical constituent with potential for inhibition of α-amylase and can be used as therapeutic purposes. In this review our efforts have been devoted to explore the mechanism based carbohydrates-hydrolyzing enzymes Inhibitors for the regulation of diabetes.